2020
DOI: 10.1111/fme.12422
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water quality, local knowledge and river–floodplain connectivity on commercial wild crayfish harvesting in the Atchafalaya River Basin

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Our work builds on recent efforts by Vargas-Lopez et al ( 2020) to better quantify the effects of environmental conditions on crawfish abundance and harvest. Vargas-Lopez et al (2020) found that floodplain connectivity plays a role in harvesters' behaviors. The positive association that we documented between river stage and harvest aligns with the findings of Vargas-Lopez et al ( 2020) on the importance of hydrology for crawfish.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our work builds on recent efforts by Vargas-Lopez et al ( 2020) to better quantify the effects of environmental conditions on crawfish abundance and harvest. Vargas-Lopez et al (2020) found that floodplain connectivity plays a role in harvesters' behaviors. The positive association that we documented between river stage and harvest aligns with the findings of Vargas-Lopez et al ( 2020) on the importance of hydrology for crawfish.…”
Section: Discussionmentioning
confidence: 99%
“…However, many other factors outside the scope of our study likely influence crawfish abundance and harvest. The exact conditions present where traps are fished, such as depth and turbidity, are known to be meaningful factors (Vargas-Lopez et al 2020), but they are not documented in landings. Market price is another factor that certainly influences effort and landings; 90% of the crawfish supply comes from aquaculture, so price may be considered an external force to the wild-capture fishery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations